2003
DOI: 10.2139/ssrn.457423
|View full text |Cite
|
Sign up to set email alerts
|

Monetary Policy Shocks and Security Market Responses

Abstract: Abstract:This paper contributes to a recent literature that tries to filter exogenous monetary policy surprises from high frequency (daily) data. The literature uses the fact that monetary policy surprises are realized only on days that the Federal Reserve changes the Federal Funds Target, or on days that the Federal Open Market Committee (FOMC) meets and does not change the target-so-called "event days". We add to the literature in three ways: (1) we specify a more general model in which security prices respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 19 publications
0
24
0
Order By: Relevance
“…Sack (2002, 2003) and Craine and Martin (2003) use a heteroscedasticitybased estimator and find a significant response of the stock market to shocks in the interest. Bernanke and Kuttner (2005) show that a hypothetical unanticipated 25-basis-point cut in the Federal funds rate target is associated with about a 1% increase in broad stock indexes.…”
mentioning
confidence: 99%
“…Sack (2002, 2003) and Craine and Martin (2003) use a heteroscedasticitybased estimator and find a significant response of the stock market to shocks in the interest. Bernanke and Kuttner (2005) show that a hypothetical unanticipated 25-basis-point cut in the Federal funds rate target is associated with about a 1% increase in broad stock indexes.…”
mentioning
confidence: 99%
“…3 Recent papers by Bernanke and Kuttner (2004), Craine and Martin (2003) and Flannery and Protopapadakis (2002) follow the same approach in regards to using only the surprise element (the difference between announcement and expectation) of news as the explanatory variable when measuring the response of the stock market to monetary policy changes and other macroeconomic news. 4 We are only investigating the impact of US monetary policy news and, therefore, we do not rescale our news variables by their respective standard deviations.…”
mentioning
confidence: 99%
“…Craine and Martin (2003) estimate a general factor model, which allows multiple sources of systematic risk, including monetary policy surprises, to affect long-term bond yields. They use daily data, as do the studies reported in lines 1-3, but use all observations instead of just those days on which policy shifts occurred.…”
Section: Results From Other Studiesmentioning
confidence: 99%
“…Single-equation studies may suffer from an omitted variable problem. Craine and Martin (2003) provide evidence that this is the case. Moreover, singleequation estimates are based on a small sample mostly from the 1990s.…”
Section: Introductionmentioning
confidence: 87%